Modelling broiler requirements for lysine and arginine - Nogueira, Bernardo Rocha Franco [UNESP]; Sakomura, Nilva Kazue [UNESP]; Reis, Matheus de Paula [UNESP]; Leme, Bruno Balbino [UNESP]; Létourneau-Montminy, Marie-Pierre; Viana, Gabriel da Silva (MDPI, 2021)
Six assays were conducted to investigate male and female broiler responses to standardized ileal digestible (SID) lysine (Lys) and arginine (Arg). Response data were modeled to estimate the efficiency of utilization (k) of both amino acids and adjust factorial models to predict bird intake for SID Lys and SID Arg. In each assay, 1280 Cobb 500® broilers (640 male and 640 female) were randomly assigned to one of sixteen dietary treatments with four replicates of 20 birds. Dietary treatments consisted of crescent levels of SID Lys or SID Arg based on the dilution technique. The values of k determined for each phase (1-to 14-, 15-to 28-, and 29-to 42-d-old) and sex were contrasted using linear regression with groups (sex and phase). The estimated efficiencies were 0.79 for Lys and 0.62 for Arg, which were unaffected by phase or sex. Factorial models based on body weight and weight gain (M1) and on body and feather protein weight and deposition (M2) were applied to estimate the SID Lys and Arg intake for growth. The amino acid intake based on M2 had a lower error of prediction. Broiler chickens require 94.9 and 92.9 mg/d of SID Lys and SID Arg to deposit 1 g of body protein.
Keywords: Amino acids; Dilution technique; Efficiency of utilization; Factorial approach